2016
DOI: 10.1101/094995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic footprint of population fragmentation and contemporary collapse in a freshwater cetacean

Abstract: 1Understanding demographic trends and patterns of gene flow in an endangered species is crucial for devising conservation strategies. Here, we examined the extent of population structure and recent evolution of the critically endangered Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis). By analysing genetic variation at the mitochondrial and nuclear microsatellite loci for 148 individuals, we identified three populations along the Yangtze River, each one connected to a group of admixed anc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…This indicates that habitat fragmentation caused by hydrological changes and human activities has affected population exchange in the main lake area, although the YFPs in the main lake area are able to move freely during the rainy season. Studies showed that females can reproduce in the natal YFP population (Chen et al, 2016). When YFPs group in a sand pit connected to the main channel by shallow waters, the population can persist for short periods.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that habitat fragmentation caused by hydrological changes and human activities has affected population exchange in the main lake area, although the YFPs in the main lake area are able to move freely during the rainy season. Studies showed that females can reproduce in the natal YFP population (Chen et al, 2016). When YFPs group in a sand pit connected to the main channel by shallow waters, the population can persist for short periods.…”
Section: Discussionmentioning
confidence: 99%